Implementation of the affirmative policy for the black population in three public universities in the South of Brazil: a long walk (Práxis Educativa, 2022)
In this work, an argument that exposes and discusses the creation of public universities in Brazil and its relationship with the education of students belonging to the families of the Brazilian white elites is presented. It is also highlighted the process of institutionalization of racial quota policy in order to establish a relationship with a global agenda, whose discussions on racial discrimination have been exerting influence on the context of institutional deracialization movements in Brazil. Initially, the university as a historical institution in Brazil is addressed; then, dialogues are established between democratic management of Higher Education and social justice. The path towards public policy for the promotion of racial equality in federal institutions of Higher Education is then observed. Finally, the scenarios of three public universities in the South of the country is presented.Keywords: Brazilian public university. Racial quotas. Black people.